The strategy, function, and efficacy of the peritexts in Giles’ and Minford’s English translations of Liaozhai Zhiyi - Liang, Zhao (Frontiers in Communication, 2024)
Among all the English translations of Liaozhai Zhiyi, Giles’ and Minford’s translations received the most reviews from Western readers. Their translations are rich in peritexts, which make up a large proportion of the two translations. Based on Genette’s Paratexts theory and Batchelor’s latest research in this field, this article examines the two translations’ peritext strategy, main functions, and efficacy in the reception of Liaozhai Zhiyi with a view to seeing the roles that two types of peritexts play in the dissemination and reception of the book in English world. Looking closer to the two translations’ peritext strategies, including covers, acknowledgments, prefaces, introductions, notes, illustrations, and appendices, the author summarizes five main functions of the peritexts: to reveal to some extent the translator’s translating aims, to show the commissioner’s peritext strategies, to spread Chinese culture, and to consciously or unconsciously manifest socio-cultural context. In addition, the article, through contrastively analyzing readers’ reviews of two translations’ peritexts, concludes that the efficacy of the peritexts in Minford’s translation is much better than that in Giles’ translation, which means that the former may, to a large degree, help promote the reception of Liaozhai Zhiyi, while the latter may not. It is also anticipated that the research pattern can be used in the study of the roles peritexts and epitexts play in the reception of a wider genre of Chinese works so as to facilitate the going-global of Chinese works and culture.